The Great Mosque of Damascus : Studies on the Makings of an Umayyad Visual Culture - Flood, Finbarr (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The celebrated Great Mosque of Damascus was built in the early eighth century by the Umayyad caliph al-Walīd b. 'Abd al-Malik. This book provides a detailed study of this Mosque. Using textual, visual, and archaeological evidence, the author attempts to reconstruct some of the basic formal and decorative features of the Umayyad mosque, to locate it within its broader urban context, and to consider its role within al-Walīd's unprecedented programme of architectural patronage. The work explores the intracultural and intercultural functions of religious architecture within an official visual discourse intended to project a distinctive Muslim identity in a manner determined by Umayyad political aspirations. It will be of particular interest to those concerned with the relationship between the Umayyad caliphate and Byzantium.